2018
DOI: 10.1016/j.molp.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Attractive but Toxic: Emerging Roles of Glycosidically Bound Volatiles and Glycosyltransferases Involved in Their Formation

Abstract: Plants emit an overabundance of volatile compounds, which act in their producers either as appreciated attractants to lure beneficial animals or as repellent toxins to deter pests in a species-specific and concentration-dependent manner. Plants have evolved solutions to provide sufficient volatiles without poisoning themselves. Uridine-diphosphate sugar-dependent glycosyltransferases (UGTs) acting on volatiles is one important part of this sophisticated system, which balances the levels of bioactive metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 94 publications
(107 reference statements)
2
109
0
1
Order By: Relevance
“…Similarly, UGT85 enzymes and UGT709Q1 (inactive) formed a separate group in the phylogenetic tree (Figure S4) supporting the functional difference. As considerable transcript levels of UGT85A73 were found in tobacco flower and the encoded protein preferentially glucosylated nonpolar, low‐molecular‐weight compounds, we proposed that this enzyme is implicated in the modification of tobacco flower volatiles (Song et al ., ). UGT85s from tea plant, grape, and kiwifruit were shown to catalyze the glucosylation of volatiles, including geraniol, citronellol, hexanol, (Z)‐3‐hexenol, octanol, 2‐phenylethanol, benzyl alcohol, and 2,5‐dimethyl‐4‐hydroxy‐3(2H)‐furanone (furaneol; Bönisch et al ., ; Song et al ., ; Jing et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, UGT85 enzymes and UGT709Q1 (inactive) formed a separate group in the phylogenetic tree (Figure S4) supporting the functional difference. As considerable transcript levels of UGT85A73 were found in tobacco flower and the encoded protein preferentially glucosylated nonpolar, low‐molecular‐weight compounds, we proposed that this enzyme is implicated in the modification of tobacco flower volatiles (Song et al ., ). UGT85s from tea plant, grape, and kiwifruit were shown to catalyze the glucosylation of volatiles, including geraniol, citronellol, hexanol, (Z)‐3‐hexenol, octanol, 2‐phenylethanol, benzyl alcohol, and 2,5‐dimethyl‐4‐hydroxy‐3(2H)‐furanone (furaneol; Bönisch et al ., ; Song et al ., ; Jing et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…As considerable transcript levels of UGT85A73 were found in tobacco flower and the encoded protein preferentially glucosylated nonpolar, low‐molecular‐weight compounds, we proposed that this enzyme is implicated in the modification of tobacco flower volatiles (Song et al ., ). UGT85s from tea plant, grape, and kiwifruit were shown to catalyze the glucosylation of volatiles, including geraniol, citronellol, hexanol, (Z)‐3‐hexenol, octanol, 2‐phenylethanol, benzyl alcohol, and 2,5‐dimethyl‐4‐hydroxy‐3(2H)‐furanone (furaneol; Bönisch et al ., ; Song et al ., ; Jing et al ., ). Biochemical analyses of the recombinant UGT709C2 protein showed that it possessed catalytic efficiency towards 7‐deoxyloganetate, a precursor of the loganin and secologanin pathway (Asada et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have shown that UGTs also play an important role in plant growth and development and in response to biological and abiotic stresses (Tiwari et al , ; Rehman et al , ). To date, only a few volatiles and their corresponding UGTs have been functionally characterized due to the presence of hundreds of UGT‐encoding genes in most plant species (Yonekura‐Sakakibara & Hanada ; Caputi et al ; Song et al ) and substrate promiscuity of UGT enzymes (Jones & Vogt, ). In contrast to the intensively studied UGTs involved in the glucosylation of monoterpenols (Bönisch et al , ,b; Yoneya & Takabayashi, ; Ohgami et al , ) and nonvolatile diterpenoids (C20) (Richman et al , ; Nagatoshi et al , ; Sun et al , ), the UGTs involved in the glucosylation of sesquiterpenes have been scarcely documented, possibly due to the relative rarity of sesquiterpene glycosides in the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have evolved numerous specialized metabolites that play essential roles in mediating interactions between plants and their habitats (Song et al ., ), and these compounds constitute a valuable resource for the discovery of economically important bioactive structures (Mithöfer & Boland, ; Shang et al ., ; Kajikawa et al ., ). Intriguingly, some plants have evolved fruit‐specific defensive chemicals to deter herbivores and prevent their fruits and seeds from being attacked by microbes (Tewksbury et al ., , ).…”
Section: Introductionmentioning
confidence: 99%